Analisis Tebal Lapis Tambah Perkerasan Lentur Pada Ruas Jalan Kolaka Rate-Rate - Vickky Anggara Ilham; Irwan Lakawa; Siti Mariam Aprillian (Sultra Civil Engineering Journal (SCiEJ), 2026)
This study aims to analyze the structural capacity of the existing pavement and to determine the required thickness of flexible pavement overlay on the Kolaka – Rate-rate Road section to adequately serve traffic loads over a 20-year design life. Based on traffic survey results, the Average Daily Traffic (ADT) indicates a dominant contribution from heavy vehicles. The calculation shows a daily Equivalent Standard Axle (ESA) value of 1,322.47 ESA/day, with the largest contribution coming from 3-axle and ≥4-axle trucks. Considering an annual traffic growth rate of 5% and a 20-year design life, the Cumulative Equivalent Standard Axle (CESA) is estimated at approximately 1.60 × 10⁷ ESA. The evaluation of the existing pavement structure yields a Structural Number (SNₑₓ) of 6.96. Based on the relationship between CESA and subgrade bearing capacity (CBR 6%), the required Structural Number (SNᵣ) is determined to be 8.50. The difference between the required SN and the existing SN results in an overlay Structural Number (SNₒᵥ) requirement of 1.54. This value is then converted into the required asphalt overlay thickness using the appropriate layer coefficient